Life, Work and Education During a Pandemic (Selected Issues from an International Perspective) - Rafał Wiktor Piwowarski (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The worldwide pandemic has far-reaching, tangible effects on life, economy, work, education and people-to-people contacts. Research Aim: The aim of article is to present and analyze the results of international research on selected issues related to COVID-19, such as unemployment, remote work, and above all - to show the impact of pandemic on broadly understood education. Evidence-based Facts: Most of publications relating to the issues connected with the current pandemic are fragmentary, concern one enviroment and generally refer to narrower issues. The available knowledge/data bases - national, regional, international - make it possible to undertake analitical studies relating to several, sometimes to several dozen countries. The analysis of several international studies allowed the article to show both the differences and similarities in the sphere of the impact of the pandemic on life and education. Summary: The article presents only some of the issues related to the effects of the pandemic on most spheres of life. New problems and studies are likely to arise. In the field of education probably there will be those in which the issues related to the quality of teaching and perception of acquired knowledge and skills should be analyzed.